Qualitative findings of students' perception on practice of sSelf-regulated strategies in online community discussion - Vighnarajah,; Wong, Su Luan; Abu Bakar, Kamariah (Elsevier Ltd, 2009)
With rapid emergence to the birth of the knowledge era, an active and interactive learning environment is fundamental to any teaching and learning process. Over time, negative implications of traditional learning environment are mounting, and measures must be taken to challenge it. With extensive research on available learning tools, it has become more feasible to provide our students with better learning opportunities. Such was the anticipation in the Malaysian educational context. Hence, this paper aims to address qualitative findings of a study on self-regulated learning strategies conveyed through the proposed interactive e-learning community (iELC). In duration of eight weeks, students (n = 50) from regular national secondary schools were subjected to online learning tasks aimed to advance strategies on self-regulated learning. To date, strategies of self-regulated learning have been perceived as key to learner to succeed academically and after the schooling years. By means of semi-structured interview, data were collected from small group and one-to-one perception. Results were directed at the overall development of self-regulated learning strategies and its diffusion in the iELC discussion platform. Conclusively, these findings add significantly to the understanding of self-regulated learning strategies in an online learning environment.